Biological Functions of ilvC in Branched-Chain Fatty Acid Synthesis and Diffusible Signal Factor Family Production in Xanthomonas campestris - Li, Kai-Huai; Yu, Yong-Hong; Dong, Hui-Juan; Zhang, Wen-Bin; Ma, Jin-Cheng; Wang, Hai-Hong (Frontiers in Microbiology, 2017)
In bacteria, the metabolism of branched-chain amino acids (BCAAs) is tightly associated with branched-chain fatty acids (BCFAs) synthetic pathways. Although previous studies have reported on BCFAs biosynthesis, more detailed associations between BCAAs metabolism and BCFAs biosynthesis remain to be addressed. In this study, we deleted the ilvC gene, which encodes ketol-acid reductoisomerase in the BCAAs synthetic pathway, from the Xanthomonas campestris pv. campestris (Xcc) genome. We characterized gene functions in BCFAs biosynthesis and production of the diffusible signal factor (DSF) family signals. Disruption of ilvC caused Xcc to become auxotrophic for valine and isoleucine, and lose the ability to synthesize BCFAs via carbohydrate metabolism. Furthermore, ilvC mutant reduced the ability to produce DSF-family signals, especially branched-chain DSF-family signals, which might be the main reason for Xcc reduction of pathogenesis toward host plants. In this report, we confirmed that BCFAs do not have major functions in acclimatizing Xcc cells to low temperatures.